“To sleep”, “to cough” and “to love’: Uncommon primary headaches - Souza, Wallyson Pablo de Oliveira (2021)
IntroductionThere are some physiological situations in which the individual may experience headache, such as to sleep, to cough and to love. In the first situation, "to sleep", the patient does not have headache when awake, but is awakened by pain during sleep; in the second, the act of "to cough" is a trigger for the onset of pain and finally, "to love," here, meaning sexual intercourse, can be a headache trigger.ObjectiveTo review the epidemiological, pathophysiological aspects and therapeutic management of headaches that arise when sleeping, coughing and having sexual intercourse.MethodA narrative review of literature including case reports and clinical trials were carried out. The articles were systematically obtained and assessed by the authors.ResultsThree primary forms considered rare were identified: hypnic headache, primary cough headache and primary headache associated with sexual activity. Hypnic headache occurs only during sleep, predominantly in women after 50 years of age. It was described in 1988 by Raskin, and has a prevalence ranging from 0.07% to 0.22%. Primary cough headache is triggered by coughing or another Valsalva maneuver and is more common in men over40 years of age. It was first described by Jules Tinel and has a prevalence of 0.4% to 1.2%. Primary headache associated with sexual activity occurs during sexual intercourse. It is more frequent in men after 40 years of age. It was described in the second century of the Christian era, by the Persian physician Avicenna. Its prevalence ranges from 0.9% to 1.6%.ConclusionPrimary headaches in the "to sleep", "to cough", and "to love" group are rare. They predominate in men, after 40 years of age, are of short duration, can be primary or secondary and have a therapeutic response to indomethacin.